Penerapan Layanan Bimbingan Kelompok Dengan Media Audio- Visual Dalam Meningkatkan Minat Belajar Siswa Kelas X Mipa V Pada Masa Pandemi Di Man Kota Palangka Raya - Nurhasanah Nurhasanah; Romiaty Romiaty (IAIN Kudus, 2021)
Application of Group Guidance Services Using Audio-Visual Media in Increasing Student Interest in Class X Mipa V During the Pandemic Period in Man City, Palangka Raya. This study aims to see the results of increased interest in learning with the application of group guidance services using audio-visual media. The study employed a descriptive quantitative approach and a method of experimentation with the design of one group of test-pretests and posttests. The study involves all X MIPA V MAN city of Palangka Raya students as a population and selection of samples by impressive sampling, selected 8 students who were used as samples. The data in this study was retrieved using 30 pest-interest items. Based on data analysis obtained after treatment of a three-time audio-visual media group guidance service, which indicates an increase in the interest of studying X MIPA V MAN city of Palangka Raya. The research found t_(count)> table (14,429 > 2,447) and sig's value (2-tailed) is of 0,000 <.05 that Ho is declined and Ha accepted. Thus summarized the application of group guidance services with visual audio media can increase the interest of studying students X MIPA V MAN city of Palangka Raya.Keywords: Group Guidance, Audio-Visual Media, Interest In Learning